How many testers are needed to assure the usability of medical devices?. (September 2014) - Borsci, Simone; Macredie, Robert D; Martin, Jennifer L; Young, Terry
<x xml:space="preserve">Abstract</x> Before releasing a product, manufacturers have to follow a regulatory framework and meet standards, producing reliable evidence that the device presents low levels of risk in use. There is, though, a gap between the needs of the manufacturers to conduct usability testing while managing their costs, and the requirements of authorities for representative evaluation data. A key issue here is the number of users that should complete this evaluation to provide confidence in a product's safety. This paper reviews the US FDA's indication that a sample composed of 15 participants per major group (or a minimum of 25 users) should be enough to identify 90–97% of the usability problems and argues that a more nuanced approach to determining sample size (which would also fit well with the FDA's own concerns) would be beneficial. The paper will show that there is no a priori cohort size that can guarantee a reliable assessment, a point stressed by the FDA in the appendices to its guidance, but that manufacturers can terminate the assessment when appropriate by using a specific approach – illustrated in this paper through a case study – called the 'Grounded Procedure'.